Lifetime changes in vocal syntactic complexity of rock hyrax males are determined by social class - Demartsev, Vlad; Kershenbaum, Arik; Ilany, Amiyaal; Barocas, Adi; Weissman, Yishai; Koren, Lee; Geffen, Eli (My University, 2019)
The ontogeny of quality-based signals has been studied in numerous animal systems but the degradation of vocal signals with age has received much less attention. Investigating age-related changes in quality-based acoustic signals and the associated social processes (e.g. rank changes, competition intensity) can expand our understanding of the information content of signals and their perception by receivers. To address this issue, we monitored the changes in syntactic complexity of songs in male rock hyraxes, Procavia capensis, over their lifetime. These songs are known to reflect the signallers' identity and quality. We found that age, residency and tenure had a combined effect on the syntactic structure of signals. Progression trends differed according to the signallers’ social status. For mature bachelor males song complexity increased with age, whereas it decreased for resident males, which had performed complex songs at the beginning of their residency tenure. This decline in complexity, potentially indicating fatigue, has also been associated with increased competition pressure, reflected in males' increased tendency to become involved in fights. In previous studies on animal vocal signalling and human speech, no effects of senescence on syntactic complexity were detected. Our current findings, however, suggest that vocal complexity is informative and could be reflective of the condition and competitive abilities of the signallers. However, an alternative explanation of lower signal complexity due to decreasing competitive motivation is also discussed.
Keywords: 570